RELATIONSHIP WITH THE LEVEL OF MASTERY LEARNING MOTIVATION OF STUDENTS COMPETENCE IN RESPONSE EMPLOYMENT OPPORTUNITIES: Research on Student Office Administration Skill Program Vocational High School District 11 Bandung - Eviyanti Ermatasari, - (2011)
Issues examined in this study is the low level of mastery of students' competency in responding to employment opportunities. Aspects under study include two variables: Student Motivation (X) and the Student Competency Mastery Level (Y). The indicator used to consist of students learning motivation and learning activities duration, frequency of learning activities; persistence on the purpose of learning; tenacity and ability to face obstacles to achieving learning objectives; devotion and sacrifice to achieve the learning objectives, level of aspiration to be achieved; level of qualification achievements or products are achieved; and direction of attitude toward the target learning activities. This research was conducted on all Office Administration class XI student of SMK Negeri 11 Bandung. This study aims to determine whether there is a relationship motivation to study with mastery level competency vocational students expertise Office Administration program at SMK Negeri 11 Bandung. Indicators used for Mastery Level of Competencies Students, in collaboration with colleagues and customers, following security procedures, occupational health and safety, to communicate via telephone, using office equipment, plan and conduct meetings, work procedures, to follow work rules appropriate environment employment, maintain and protect the culture of work, handle incoming and outgoing mail (mail handling), recorded dictation to prepare a script, produce a simple document, and create and develop the script for the document. This study uses descriptive methods, data collection techniques with studying the documentation and dissemination of the questionnaire. The instrument used was a questionnaire with a Likert scale model of data analysis used were correlation analysis. This study used a purposive sample that is by taking the entire class XI student, amounting to 76 people. The data analysis technique used was Product Moment correlation. From the data analysis known that the coefficient of correlation between students 'motivation variable to variable levels of mastery of students' competency in a category enough. The coefficient of correlation between students' motivation variable to variable levels of student competency mastery if confirmed by the criteria of rejection of the hypothesis, suggesting that H1 is accepted and H0 is rejected. The results showed that motivation to learn Students have a positive relationship with the level of student mastery of competencies.